Analysis of Oil Leaking from Bowl on The LO Purifier Alfa Laval P626 at MV. SEAPEAK GLASGOW LNGC - Bagas Putra Darmawan; Agus Prawoto; Teguh Pribadi; Antonius E. Kristiyono; Shofa D. Robbi; Imam Sutrisno (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
Lubrication oil purifiers are essential for the optimal performance and longevity of marine engines. On board the MV. SEAPEAK GLASGOW, we encountered an issue with the Alfa Laval purifier, where alarm A57 indicated an oil leak from the bowl, accompanied by a drop in PT4 pressure and reduced bowl speed. This investigation aimed to identify the root causes of the leakage and recommend maintenance strategies to prevent future occurences. Using a qualitative approach, we conducted onboard observations, interviews with the third engineer, and a review of maintenance records. A fishbone diagram analysis revealed several contributing factors, including wear on the water block filter, scale buildup on internal components, and a lack of understanding of maintenance procedures among the engineering staff. The findings underscored that neglecting structured maintenance schedules and inadequate routine monitoring resulted in system inefficiency. As a corrective measure, an auxiliary filtration system was installed to protect and reduce scale accumulation. To further mitigate these issues, we recommend aligning maintenance activities with the purifier’s running hours and increasing the frequency of pressure checks. These actions will help minimise the risk of oil leaks and ensure consistent performance.